BRĂILA MOSQUES OF THE OTTOMAN PEROID - Gabriel Florin Ghinea (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi)
After the military expedition against Petru Raresh (1527-1538) in the Taurus, Brăila was annexed to the Ottoman Empire in 1539 and, according to contemporary sources, a fortress was built there. From that moment on, the city and its surroundings underwent a process of Islamisation. According to the 1570 census, there were 116 Muslim households in the city and four mosques. With the Islamisation of the city, the number of Muslim places of worship increased over time. At the beginning of the 19th century, there were 38 different mosques in Brăila, although some of them were destroyed. The year 1829 was an important year in the history of the city. In this year, the city came under Russian and Vlach rule, and thus the face of the city changed. In this period when a new city was being created, the identity of the city changed and the mosques and masjids from the old periods lost their functions as there was no more Muslim population in the region. Some of these buildings were demolished and some were used for other purposes, even for a short time. Only one of these mosques was rescued, restored and converted into the Church of the Holy Archangels Michael and Gabriel in the centre of the city. Due to the scarcity of information on Muslim places of worship in Brăila in the Ottoman period, there is no study on this subject yet. The information published in the studies on Brăila supported by the data collected from Romanian and Ottoman archival documents, has been brought together in this article and presented to the attention of the scholarly world.